Electromagnetic Wave Absorption Performance Of Carbon Nanocoils By Using Mixed Ferrites As Catalyst - Fadzidah Mohd Idris; Ts. Dr. Hatika Kaco; Siti Munirah Mohd; Nurhidaya Mohamad Jan; Haslinawati Mohd Mustapha; Zanariah Mohd Idris (Erzincan Binali Yıldırım University Graduate School of Natural and Applied Science., 2024)
Non-Indexed Publication